2016
DOI: 10.1186/s40880-016-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation: advances and controversies

Abstract: The management of localized breast cancer has changed dramatically over the past three to four decades. Breast-conserving therapy, which involved lumpectomy followed by adjuvant irradiation, is now widely considered the standard of care in women with early-stage breast cancer. Accelerated partial breast irradiation (APBI), which involves focal irradiation of the lumpectomy cavity over a short period of time, has developed over the past two decades as an alternative to whole breast irradiation (WBI). Multiple A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(38 reference statements)
0
11
0
1
Order By: Relevance
“…One of the limitations of our study is the use of 'classic' external beam radiotherapy. Though it is still commonly in use, the forefront in radiotherapy is shorter treatment protocols, intra-surgical radiation and others ( 23 ). Also, it needs to be considered that the intention of the paper was not to provide information on disease-free survival even though the number of patients was fair, but to show the necessity of marking the tumor bed with clips in order to make radiotherapy more precise.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of our study is the use of 'classic' external beam radiotherapy. Though it is still commonly in use, the forefront in radiotherapy is shorter treatment protocols, intra-surgical radiation and others ( 23 ). Also, it needs to be considered that the intention of the paper was not to provide information on disease-free survival even though the number of patients was fair, but to show the necessity of marking the tumor bed with clips in order to make radiotherapy more precise.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found that patients treated with this method had higher rate of mastectomy, when compared to patients treated with the WBI (17). Other studies have noted the increased rates of complications, such as fatt y necrosis and rib fractures (5).…”
Section: Efficacy and Side Effects Of Pbimentioning
confidence: 98%
“…In the case of the whole breast irradiation (WBI) the side eff ects involve the entire breast, as opposed to the partial breast irradiation (PBI), in which the target volume is much smaller. Further rationale for PBI off ers the data that as much as 68% of ipsilateral recurrences occur within 3 cm radius around the tumor bed (5). This, in addition to the fact that the smaller treatment volume allows for the application of higher total radiation dose, this enabling even further shortening of the RT course, has prompted the idea of PBI.…”
Section: Introductionmentioning
confidence: 99%
“…This type of radiation can be delivered using several techniques: (I) interstitial brachytherapy (high dose rate, pulsed dose rate, permanent implants); (II) brachytherapy using the balloons (Mammosite ® , Contura ® ); (III) hybrid brachytherapy devices [strut-adjusted volume implant (SAVI) applicator]; (IV) external beam radiotherapy (3D, IMRT, VMAT); or (V) intraoperative radiotherapy with electrons or X-rays, (detailed below). A review of these techniques and associated controversies has been reported elsewhere (66,67). © Gland Surgery.…”
Section: Apbimentioning
confidence: 99%